2020
DOI: 10.1007/s11698-020-00216-z
|View full text |Cite
|
Sign up to set email alerts
|

New estimation of the gross domestic product in Baltic countries in 1913–1938

Abstract: Using the demand-side approach we provide new estimates of output per capita for Estonia, Latvia, and Lithuania in 1913, 1922. Our findings suggest that the levels of real output per capita in Estonia and Latvia were much above the all-Russian mean in 1913. In 1938, the output per capita of Estonia and Latvia surpassed the prewar level by up to 20%, but the total output of Latvia did not reach this mark because of population reduction. Structural changes in the interwar Estonian and Latvian economies explain l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(1 citation statement)
references
References 29 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…This argument was explicitly aimed at the religious poor. Bearing in mind the economic difficulties of the postwar and new independence era, these costs would have been potentially significant (Norkus and Markevičiūtė 2020;Valge 2006). However, looking at the results of the referendum, the previous analysis concluded that this tactic seemed to have had little or no effect, especially in the countryside.…”
Section: Does Voting Against Religious Studies Suggest Secularization?mentioning
confidence: 99%
“…This argument was explicitly aimed at the religious poor. Bearing in mind the economic difficulties of the postwar and new independence era, these costs would have been potentially significant (Norkus and Markevičiūtė 2020;Valge 2006). However, looking at the results of the referendum, the previous analysis concluded that this tactic seemed to have had little or no effect, especially in the countryside.…”
Section: Does Voting Against Religious Studies Suggest Secularization?mentioning
confidence: 99%